2020
DOI: 10.1038/s41598-020-63936-2
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuroprosthesis improves postural stability during Sensory Organization Test in lower-limb amputees

Abstract: To maintain postural stability, unilateral lower-limb amputees (LLAs) heavily rely on visual and vestibular inputs, and somatosensory cues from their intact leg to compensate for missing somatosensory information from the amputated limb. When any of these resources are compromised, LLAs exhibit poor balance control compared to able-bodied individuals. We hypothesized that restoring somatosensation related to the missing limb via direct activation of the sensory nerves in the residuum would improve the standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 80 publications
(84 reference statements)
3
43
1
Order By: Relevance
“…This process was repeated at the beginning of each testing session to minimize the influence of confounding factors, such as insole placement within the shoe. More in-depth details about stimulation parameter tuning can be found in Charkhkar et al 39 .…”
Section: Closed-loop Sensory Neuroprosthesis To Deliver Neural Stimumentioning
confidence: 99%
“…This process was repeated at the beginning of each testing session to minimize the influence of confounding factors, such as insole placement within the shoe. More in-depth details about stimulation parameter tuning can be found in Charkhkar et al 39 .…”
Section: Closed-loop Sensory Neuroprosthesis To Deliver Neural Stimumentioning
confidence: 99%
“…The interventions that specifically target the sensory mechanisms have shown to be effective in improving standing balance. E.g., Charkhkar et al (2020) showed that the enhanced perception of the plantar pressures under the prosthetic feet achieved using artificial sensory feedback can significantly improve the postural stability of lower limb amputees. Similarly, Petrini et al (2019) showed that real-time tactile and proprioceptive feedback provided by sensory neuroprosthetic promoted improved mobility, fall prevention, and agility during active tasks in transfemoral (above-knee) amutees.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate but slow movements can be generated for high-dimensional artificial hands with wrist and digits; however, the accuracy is challenged by changing limb posture and orientation. One potential solution is the use of closed-loop control systems that provide not only the forward control of prosthetic, but also incorporate the sensory feedback within neuroprosthetics (Charkhkar et al, 2020; Ganzer et al, 2020; Hughes et al, 2020). The closed-loop control system that takes into account muscle forces will likely require accurate representation of musculoskeletal actions, which are essential for the description of both muscle forces and sensory signals responsible for proprioception.…”
Section: Discussionmentioning
confidence: 99%